CORONARY STENTING IN INDIVIDUALS WITH ISCHEMIC HEART DISEASE AND CONCOMITANT ONCOLOGICAL DISEASES (Modern American Journal of Medical and Health Sciences, 2025)
Coronary heart disease and cancer are leading causes of death worldwide. The combination of coronary heart disease (CHD) and oncopathology , given the prevalence of both nosologies, is not uncommon [2]. The presence of concomitant coronary artery disease in patients with malignant neoplasms in most cases serves as an aggravating factor, complicating and/or limiting the treatment of oncopathology [1]. Coronary artery disease in patients with oncopathology can increase the incidence of postoperative complications, in-hospital mortality, and also reduce long-term survival after radical surgery for malignant neoplasm. Myocardial revascularization , performed as the first stage in patients with hemodynamically significant coronary artery (CA) stenosis, is the main treatment method preventing the development of cardiovascular complications during and after oncopathology treatment .